Solid Lipid Nanoparticles as Novel Carriers for Enhancing Classical Antifungal Therapies - Sadule Akshay S; Dr. Sameer Shafi; Komal Jadhav; Vijay Shinde; Punam Londhe (Asian Journal of Pharmaceutical Research and Development, 2024)
Fungi are increasingly recognized as significant human pathogens, making effective diagnosis and treatment crucial. While the introduction of new antifungal agents over the past two decades has advanced treatment options, rising drug resistance presents a challenge. Nanoparticles (NPs) have emerged as a promising solution for delivering antifungal drugs, offering greater inhibitory effects at lower concentrations compared to traditional antibiotics. Key issues such as reduced efficacy, limited tissue penetration, poor solubility, and decreased bioavailability often hinder antifungal treatments. Incorporating antifungal drugs into various NP delivery systems aims to overcome these limitations. This review discusses different types of NPs used for antifungal delivery and highlights their advantages over conventional drugs.